Sanksi Adat Dayak Mualang dan Jangkang di Kabupaten Sekadau dalam Kaitannya dengan Konsep Residive Dan Asas Ne Bis In Idem - Mukti, Plasma Versiana; Herlina; Hertini, Mega Fitri; Yuliana (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research examines the sanctions imposed in the customary law system of the Dayak Mualang and Jangkang communities in Sekadau Regency, focusing on their relation to the concepts of recidivism and the principle of Ne Bis in Idem. The background arises from recurring criminal acts such as theft, domestic violence, and violations of public order, which highlight the limitations of customary sanctions in deterring repeat offenses. The study aims to analyze, first, the recognition and application of recidivism within these communities and its impact on repeated offenses; and second, the factors underlying the imposition of double sanctions for a single act in the absence of Ne Bis in Idem. Using an empirical juridical method, data were collected through field research, interviews with customary leaders, and analysis of legal documents. The findings reveal that the customary law of Dayak Mualang and Jangkang does not recognize recidivism, resulting in repeated offenders receiving the same sanctions without aggravation. Moreover, in certain cases, offenders are subjected to double sanctions by different customary authorities, which is viewed socially as moral accountability rather than legal duplication. However, this practice contradicts modern criminal law principles and creates potential violations of human rights due to legal uncertainty. The research concludes that integrating the principles of recidivism and Ne Bis in Idem into customary law is essential to enhance justice, ensure proportional sanctions, and maintain social harmony in multicultural communities.